Authoritarianism, Populism, and the Global Retreat of Democracy: A Curated Discussion. (January 2023) - Adler, Paul S.; Adly, Amr; Armanios, Daniel Erian; Battilana, Julie; Bodrožić, Zlatko; Clegg, Stewart; Davis, Gerald F.; Gartenberg, Claudine; Glynn, Mary Ann; Aslan Gümüsay, Ali; Haveman, Heather A.; Leonardi, Paul; et al.
To the surprise of many in the West, the fall of the USSR in 1991 did not lead to the adoption of liberal democratic government around the world and the much anticipated "end of history." In fact, authoritarianism has made a comeback, and liberal democracy has been on the retreat for at least the last 15 years culminating in the unthinkable: the invasion of a democratic European country by an authoritarian regime. But why does authoritarianism continue to spread, not only as an alternative to liberal democracy, but also within many liberal democracies where authoritarian leaders continue to gain strength and popularity? In this curated piece, contributors discuss some of the potential contributions of management scholarship to understanding authoritarianism, as well as highlight a number of directions for management research in this area.